Analysis of Problem Solving Ability Mathemathics Assessed from Student's Authorized Style - Dewi Saputri Arepan (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2020)
This study aims to determine the results of the analysis of students 'problem-solving abilities with Field Dependent and Field Independent cognitive styles in solving students' mathematical problems. The location of this research was conducted at SMP Negeri 4 Ambarawa. This research is a descriptive qualitative research. The determination of research subjects was based on the results of the GEFT test developed by Witkin (1973). The data was collected by means of tests and interviews, qualitative data analysis was carried out with the data reduction stage, the data presentation stage, and the conclusion / verification stage. The results of this study indicate that the students' mathematical problem-solving abilities with a field dependent cognitive style are good at understanding the problem and checking again, in the sufficient category at the problem planning stage, and in the poor category at the stage of implementing the completion plan. And the students' mathematical problem solving abilities with a field independent cognitive style were categorized as good at the stage of understanding the problem, planning for completion, carrying out solutions, and in the sufficient category at the stage of re-checking.